Effects of Carbamate Insecticides using Carbofuran Active Ingredients on Blood Glucose Levels of Wistar White Rats (Rattus norvegicus) - Nurul Tri Isnaini; Soebiyanto Soebiyanto; Dian Kresnadipayana (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2022)
Carbofuran is carbamate pesticides that kills insects, mites, and nematodes on contact or after consumption. The use of pesticides according to the rules is beneficial for farmers unless it can cause poison, health problems, environmental pollution, and residues in food products. If exposed, it causes health problems characterized by an increase in blood glucose levels. This study aims to identify the effect of carbamate insecticides using active ingredients of carbofuran on blood glucose levels of white Wistar (Rattus norvegicus) rats.This study used male Wistar strain rats. It included 3 treatment groups and 1 negative control group. Treatment group 1 used a dose of 0.5mg/kgBW rats; treatment group 2 used a dose of 1.0mg/kgBW rats; treatment group 3 used a dose of 1.5mg/kgBW rats; and control group used distilled water. The treatment was for 28 days. The blood glucose levels were checked using the Konelab 20 Clinical Chemistry Analyzer per week. Data were presented in tables, figures, and statistical analysis with SPSS 26.The results of showed the average blood glucose levels from week 0 to week 4 in group K1 (76.00; 71.00; 74.60; 75.60; 76.80 mg/dL), P1 (90.40; 91.60; 89.80; 84.80; 67.20 mg/dL), P2 (72.75; 85.00; 88.50; 58.50; 68.25 mg/dL), and P3 (82.75; 93.00; 100.25; 106.50; 117.75 mg/dL). Data analysis used the One Way ANOVA test with p-values of 0.035 (p <0.05) indicating significant differences in blood glucose levels in treatment group 3. It can be concluded that carbofuran affects blood glucose levels of rats in treatment group 3.